2021
DOI: 10.1371/journal.pone.0244699
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of the UDP-GlcNAc: PI α1–6 GlcNAc-transferase subunits of the glycosylphosphatidylinositol biosynthetic pathway of Trypanosoma brucei

Abstract: The first step of glycosylphosphatidylinositol (GPI) anchor biosynthesis in all eukaryotes is the addition of N-acetylglucosamine (GlcNAc) to phosphatidylinositol (PI) which is catalysed by a UDP-GlcNAc: PI α1–6 GlcNAc-transferase, also known as GPI GnT. This enzyme has been shown to be a complex of seven subunits in mammalian cells and a similar complex of six homologous subunits has been postulated in yeast. Homologs of these mammalian and yeast subunits were identified in the Trypanosoma brucei predicted pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…That means that ARV1 is functionally required for CD55-dependent GPI upregulation. Furthermore, the authors also show that ARV1 is associated with GPI-GlcNAc transferase, the first enzyme in the pathway, as previously observed in the trypanosome and yeast ( 9 , 10 ). This result provided evidence that upregulation of GPI synthesis occurs at an early step of the pathway, as confirmed through the study of the metabolic flux of GPI synthesis using radioactive precursors ( 9 , 10 ).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…That means that ARV1 is functionally required for CD55-dependent GPI upregulation. Furthermore, the authors also show that ARV1 is associated with GPI-GlcNAc transferase, the first enzyme in the pathway, as previously observed in the trypanosome and yeast ( 9 , 10 ). This result provided evidence that upregulation of GPI synthesis occurs at an early step of the pathway, as confirmed through the study of the metabolic flux of GPI synthesis using radioactive precursors ( 9 , 10 ).…”
supporting
confidence: 74%
“…Furthermore, the authors also show that ARV1 is associated with GPI-GlcNAc transferase, the first enzyme in the pathway, as previously observed in the trypanosome and yeast ( 9 , 10 ). This result provided evidence that upregulation of GPI synthesis occurs at an early step of the pathway, as confirmed through the study of the metabolic flux of GPI synthesis using radioactive precursors ( 9 , 10 ). Together, these pieces of evidence led the authors to propose that ARV1 may balance the rate of GPI synthesis to be needed in an early step of the pathway by somehow sensing the accumulation of the specific GPI anchor signal peptide CD55 in the ER.…”
supporting
confidence: 74%
“…Although this was based on a single unique peptide, and is therefore not a high-confidence assignment, this is the only proteomic dataset deposited on TriTrypDB ( Aslett et al, 2010 ) that identified TbFUT1. A quantitative proteomic analysis that estimated protein turnover in T. brucei ( Tinti et al, 2019 ), and ranking of protein abundances using those deep proteomic data sets ( Ji et al, 2021 ), did not identify TbFUT1 in either BSF or PCF, suggesting that it is a very low-abundance protein. The immunofluorescence analysis performed in this study does not allow us to define the specific localization of TbFUT1 in the parasite mitochondrion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutations in human ARV1 cause symptoms similar to inherited GPI de ciencies, indicating that human ARV1 is also involved in GPI biosynthesis 57,58 . A recent study in the African trypanosome Trypanosoma brucei showed that an Arv1like protein (TbArv1) is pulled down by TbGPI3, the mammalian homolog of which is PIGA 59 . Using a combination of RoseTTAFold and AlphaFold, a study to predict protein assemblies with two to ve components in S. cerevisiae also predicted that ARV1 may interact with Gpi1, the yeast homologue of mammalian PIGQ 60 , suggesting that ARV1 may form a complex with GPI Nacetylglucosaminyltransferase (GPI-GnT), the rst enzyme in the pathway (Figure S1).…”
Section: Discussionmentioning
confidence: 99%